Removal of heavy metals from water using engineered hydrochar: Kinetics and mechanistic approach - Kannan, N.; Bandala, E.R.; Zhang, Z.; Mundree, S.; Goonetilleke, A. (Elsevier, 2021)
The isotherm, kinetics, and thermodynamics parameters, and mechanisms involved in the adsorption of Pb2+ and Cu2+ ions from an aqueous solution using engineered hydrochar were investigated. The hydrochar was produced through catalytic hydrothermal carbonization of rice straw at 200 ◦C with (engineered hydrochar) and without (hydrochar) FeCl3 (1.2 %) as iron catalyst which has been reported to have the ability to enhance surface properties. Batch experiments were conducted to examine the effect of sorbent dosage, pH, and initial metal ion concentration on the adsorptive performance. The results obtained revealed that the addition of iron catalyst increased the surface functional groups, and exhibit better adsorptive performance compared to non-treated hydrochar. The adsorptive performance of engineered hydrochar was higher for Pb2+ compared to Cu2+, which can be explained by surface complexation, cationic- π interaction, and mass diffusion process with the initial removal performance limited by mass transfer process. The Langmuir isotherm model gave the best fit for the adsorption of both metals compared to the other models tested. The adsorption kinetics followed the Lagergren’s pseudo-second order model. Thermodynamic parameters revealed that Pb2+ and Cu2+ adsorption by engineered hydrochar is a spontaneous and endothermic process. Moreover, this study created new knowledge by providing an in-depth understanding of the effect of iron catalyst on the functional properties of engineered hydrochar and its adsorption mechanisms. Research on the use of catalysts in engineered hydrochar for pollutant removal is very limited. In addition, the study outcomes would contribute to the production of highly efficient magnetic hydrochars.
Keywords: Hydrochar; Heavy metals; Adsorption; Water treatment